Ritual Functions of Sun Wukong’s Hair in Wu Cheng-en’s novel “Journey to the West” - N. E. Seibel (Научный диалог, 2021)
The results of the motivational analysis of Wu Cheng-en’s novel “A Journey to the West” are presented, the mythological meanings of individual object-material images are studied, a set of ritual actions related to hair is considered: pulling out wool, casting a spell, turning around. The idea of a variety of ritual functions of hair, endowed with mystical properties in many mythological systems, is taken as a starting point; they are included in thanatal, carnival and other contexts. It has been proven that all rituals related to hair in the novel combine the archetypal meanings of being chosen, initiation, carnival buffoonery and spiritual formation. A typology of ritual functions of hair and associated miracles is proposed. The first of the selected types of metamorphosis is carried out through manipulations that Sun Wukong masters in training with the sages: this is the creation of a copy of an object or creature with the help of which the hero avoids danger. The second object of the typology is a gift from the Bodhisattva Guanyin, which requires a certain inner work from the hero — choice, bargaining, creating a new object without a ready-made sample. The question is raised about the divine leadership of the process of becoming a hero.